A synopsis of Actenosigynes Moure, Graf & Urban, 1999 (Hymenoptera: Colletidae)new species, possible oligolecty and biogeographic comments - Silveira, Fernando A. (Zootaxa, 2009)
A second species of Actenosigynes from the Mantiqueira mountain range, in the southeastern Brazilian state of Minas Gerais, is described. This new taxon can be readily distinguished from the type species of the genus, A. fulvoniger (Michener, 1989), by its entirely black-pubescent mesosoma and by the light-yellow pilosity on its terga, among other characters. Females of the two known species are illustrated for the first time and a key is presented for their identification. Analysis of the pollen extracted from the scopa of the holotype of the new species and field observations of A. fulvoniger indicate that both species of Actenosigynes are oligolectic on flowers of Loasaceae as pollen sources. This presumed couple of sister species is the first example of a speciation event related to the isolation of populations of temperate and subtropical bee species on the top of southeastern-Brazilian mountains. It suggests that complexes of sibling species may exist among the other bee species with similar disjunct distribution.